2021
DOI: 10.3390/app11115039
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Smart Helmet in Applied Sciences: A Systematic Review

Abstract: A smart helmet is a wearable device that has attracted attention in various fields, especially in applied sciences, where extensive studies have been conducted in the past decade. In this study, the current status and trends of smart helmet research were systematically reviewed. Five research questions were set to investigate the research status of smart helmets according to the year and application field, as well as the trend of smart helmet development in terms of types of sensors, microcontrollers, and wire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Incorporating BIM into safety management provides an additional comprehensive and proactive approach to identifying and mitigating potential safety hazards and risks, including the safety precautions that may be taken (Fargnoli & Lombardi, 2020). This results in a safer working environment for workers and improved collaboration and communication among stakeholders, including architects, engineers, contractors, and safety managers ( Smart helmets, which contain a variety of electronic gadgets and sensors, are being increasingly utilised in the construction sector to identify workplace hazards, location tracking, real-time monitoring, and danger alarms for workers (Choi & Kim, 2021). Smart helmets contain a range of sensor devices that allows construction companies and managers to accumulate real-time data for data analysis to lower job-related risks and enhance safety.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating BIM into safety management provides an additional comprehensive and proactive approach to identifying and mitigating potential safety hazards and risks, including the safety precautions that may be taken (Fargnoli & Lombardi, 2020). This results in a safer working environment for workers and improved collaboration and communication among stakeholders, including architects, engineers, contractors, and safety managers ( Smart helmets, which contain a variety of electronic gadgets and sensors, are being increasingly utilised in the construction sector to identify workplace hazards, location tracking, real-time monitoring, and danger alarms for workers (Choi & Kim, 2021). Smart helmets contain a range of sensor devices that allows construction companies and managers to accumulate real-time data for data analysis to lower job-related risks and enhance safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Smart helmets contain a range of sensor devices that allows construction companies and managers to accumulate real-time data for data analysis to lower job-related risks and enhance safety. Smart helmets can allow for voice contact between safety managers and workers in order to alert them of unsafe behaviour and potential risks or incidents (Choi & Kim, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of ITS, studies on helmets equipped with sensors (smart helmets) are being studied [21][22][23]; however, such studies have been limited to detecting alcohol for motorcycle riders, collision detection, and confirming the safety of riders following an accident.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated the potential applications of smart helmets in diverse scenarios, such as industry, first responder applications, and health tracking [ 11 ]. For instance, the construction industry has adopted the use of smart helmets for health and safety management by monitoring workplace surroundings or the physiological signals of workers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%